The Pattern of viral seromarkers in patients with elevated plasma creatinine of ≥ 3.5mg/dl - Olaniyan, Mathew Folaranmi; Ojediran, Tolulope Busayo; Ozuruoke, Donatus FN (Nepalese Medical Journal, 2020)
Introduction: Viral seromarkers are expressed in the serum or plasma to indicate viral infection while chronic viral infections may lead to organ failures and also kidneys have receptors as a point of entry for some viruses. This work was therefore designed to characterize viral seromarkers in patients with elevated plasma creatinine of ≥ 3.5mg/dl to determine the possible contribution of viral infections to renal disease as elevated creatinine is an index of renal disease. Materials and Methods: The study population included 62 patients aged 41 – 75 years with elevated plasma creatinine of 3.9± 0.4 mg/dl as test subjects and 100 age-matched volunteers with normal plasma creatinine of 0.8±0.2mg/dl as control subjects. Anti-HCV, HBsAg, HBeAg, and HIV; HIVp24Ag/Ab were determined in the subjects by ELISA while plasma creatinine was measured by spectrophotometry. Results: The viral seromarkers obtained in the subjects include:14.5%(09) Anti-HCV; 4.8%(03) p24Ag/Ab; 22.3%(14) HBsAg and 25%(16) HBeAb in the patients with plasma creatinine of 3.9 ± 0.4 mg/dl while 5%(05) Anti-HCV; 2%(02) p24Ag/Ab ; 12%(12) HBsAg and 18%(18) HBeAb were obtained in subjects with plasma creatinine of 0.8±0.2mg/dl. Conclusions: There was a significant relationship between viral infection and renal disease (suggested by elevated plasma creatinine) as the expression of viral seromarkers of antiHCV, HBsAg, HBeAg, and HIV; HIVp24Ag/Ab in this work were more in patients with plasma creatinine of 3.9 ± 0.4 mg/dl than subjects with plasma creatinine of 0.8±0.2mg/dl while HBsAg and HBeAg were found to be more frequent.